The Relationship between Self-determination, Career Motivation, and Conscientiousness in Teacher Education: Career Motivation, Conscientiousness, ELT, Pre-service Teacher Education, Selfdetermination Theory - Kurt, Ali; Topkaya, Ece Zehir (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Teacher quality is determined by several internal and external factors such as motivation, personality, teacher education programs, and policymaking. Developing insights into how and to what extent these factors interact with one another informs stakeholders in teacher education helping them evaluate and shape the conditions, approaches, content, and practices. This study examined the interplay between autonomy, competence, relatedness, conscientiousness, and career motivation within the framework of Self-Determination Theory (SDT), a macro-motivational theory, among pre-service English language teachers (PSTs) at a university. Utilizing a sequential mixed-method approach, quantitative data from 271 participants were analyzed, supplemented by semi-structured interviews with 17 students. The findings revealed low to moderate correlations among constructs, with notable moderate correlations between competence and conscientiousness (r=.42, p<.01), along with competence and relatedness (r=.38; p<.01). Qualitative insights corroborated these findings, highlighting that relatedness is the weakest factor with a negative connection to career motivation due to poor lecturer-student relationships. The study emphasizes the critical role of faculty-driven education in enhancing PSTs' competence and underscores the need for fostering a supportive educational environment that promotes autonomy and conscientiousness. Recommendations include enhancing teacher education practices to support self-determined motivation and addressing the negative impacts of inadequate lecturer-student relationships on educational outcomes